Islamic Philanthropy as a Deterrent to Potential Fraud - Nanang Setiawan; Muhammad Nizarul Alim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
This study aims to investigate the utilization of Islamic philanthropic institutions in Indonesia and to recommend fraud-prevention warning signals. This study employs the desk study method to conduct qualitative research with The Allocation to Collection Ratio (ACR), the disbursement speed, and the Amil Right Ratio (RHA) as early warning signals for the possibility of fraud. Data was collected from eight Islamic charitable organizations in Indonesia. Using the ACR method, the results indicated that Badan Amil Zakat Nasional (BAZNAS), Dompet Dhuafa (DD), Institut Zakat Indonesia (IZI), Lazis Muhammadiyah (Lazismu), and Baitul Maal Muamalat (BMM) have a greater potential for fraud based on higher deposited cash balances exceeding 10 percent (11-30 percent ). Due to the lack of sufficient data on website searches and financial reports, the assessment of disbursement speed is not covered in this study. Other results indicated that using the RHA method, the only institution with a RHA greater than 12.5% is RZ (RHA 13.8%), which has a greater potential for fraud due to the orientation of the institution's responsibility towards the institution's interests rather than the interests of non-amil mustahik. This study contributes to providing an overview of the use of funds in Islamic philanthropic institutions and fraud warning signs in order to anticipate and prevent potential fraud.==================================================================================================== ABSTRAK – Filantropi Islam Sebagai Pencegah Potensi Fraud. Studi ini ditujukan untuk mengeksplorasi pendayagunaan lembaga filantropi Islam di Indonesia dan memberikan rekomendasi warning signals sebagai upaya pencegahan terhadap potensi fraud. Studi ini merupakan penelitian kualitatif menggunakan metode desk study dengan tiga metode sebagai warning signal terhadap potensi fraud: metode ACR (Allocation to Collection Ratio), Disbursement Speed dan Rasio Hak Amil (RHA). Studi ini menggunakan objek data delapan lembaga filantropi Islam di Indonesia. Hasil studi menunjukkan melalui metode ACR: Badan Amil Zakat Nasional (BAZNAS), Dompet Dhuafa (DD), Institut Zakat Indonesia (IZI), Lazis Muhammadiyah (Lazismu) dan Baitul Maal Muamalat (BMM) memiliki potensi fraud yang lebih tinggi didasarkan pada saldo kas yang mengendap lebih tinggi di atas 10% (11-30%). Penilaian disbursement speed tidak dijelaskan dalam studi ini dikarenakan tidak adanya informasi yang memadai pada penelusuran website dan laporan keuangan. Hasil studi lainnya menunjukkan melalui metode RHA, satu lembaga dengan RHA >12,5% adalah RZ (RHA 13,8%) memiliki potensi fraud lebih tinggi didasarkan pada orientasi tanggungjawab lembaga yang lebih berpihak kepada kepentingan lembaga daripada kepentingan pihak mustahik non ‘amil. Studi ini berkontribusi memberikan gambaran pendayagunaan dana pada lembaga filantropi Islam, memberikan warning signal terhadap potensi fraud untuk mengantisipasi dan meminimalisir terjadinya potensi fraud.